Optimal Trajectory Optimization of 7R Robot for Space Maintenance Operation - Qidong Li; Hehua Ju; Pengfei Xiao; Feifei Chen; Fei Lin (IEEE Access)
This paper studies the optimal trajectory optimization of a space robot for maintenance operations. A new trajectory planning algorithm is proposed to solve the problems of low maintenance efficiency and poor stationarity of space robots on-orbit. Firstly, considering the constraint conditions such as the speed, acceleration and secondary acceleration of each joint of the space robots, the cubic spline curve is used to plan the trajectory of the space robots in the joint space. Then, a comprehensive optimal planning model for time-jerk is established, and the optimal problem of space maintenance efficiency and stationarity is described as a nonlinear constrained optimization problem. Finally, a hybrid optimization algorithm is proposed to solve the trajectory optimization problem of space robots by combining genetic algorithm and particle swarm optimization method. The simulation results show that, compared with several classic optimization algorithms, the proposed hybrid optimization algorithm can obtain a better maintenance trajectory of the space robots under the constraints, which solves the low efficiency and poor stability of the space robots on-orbit maintenance problem.